Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank (World Bank, Washington, DC, 2018)
The main body of the report is organized in two chapters with one annex. Chapter one focuses on recent economic developments in the real, fiscal and banking sectors, while providing a near term outlook that highlights critical challenges facing the Palestinian economy. Chapter two provided input on a vision for Gaza development including performance of the Gaza economy, living standards of the people of Gaza and strategy for Gaza development. It explores the nature of the decline of the Gazan economy and identifies the needs going forward. The annex assesses the status of the World Bank recommendations to the AHLC meeting over the years. The annex discusses fiscal sustainability, economic development and Gaza reconstruction and recovery.